Opportunities and Challenges of Nepal’s Health Systems: A Critical Study in Federal Context - Dahal, Kabita (Journey for Sustainable Development and Peace Journal, 2024)
This paper aims to analyze the health system in Nepal by exploring different opportunities and challenges. It takes an integrated approach to define and analyze the health system. The paper employs secondary sources of data and then follows a systematic review approach. The major findings include that the health system in Nepal is making remarkable progress after the federal system was adhered to in 2015, and there are several opportunities with changing political and economic contexts. However, some policy-level issues, problems related to health governance, issues of skilled and professional human resources, poor financing, weak regulatory and monitoring systems, and community empowerment are some of the critical challenges to addressing the health system in Nepal. The conclusions of the paper can contribute to the policymakers, health researchers, and health professionals in Nepal and beyond.